A Comprehensive Evaluation of Health-Related Life Quality Assessment Through Head and Neck, Prostate, Breast, Lung, and Skin Cancer in Adults - Jalili, Shirin; Ghasemi Shayan, Ramin (Frontiers in Public Health, 2022)
Health assessment data assists the well-being and patient care teams' process in drawing up a care and assistance plan and comprehending the requirements of the patient. Comprehensive and precise data about the Quality of Life of cancer patients play a significant part in the development and organization of cancer patient care. Quality of Life has been used to mean a variety of various things, such as health situation, physical function, symptoms, psychosocial modification, well-being, enjoyment of life, and happiness. Chronic diseases such as cancer are among the disorders that severely affect people's health and consequently their Quality of Life. Cancer patients experience a range of symptoms, including pain and various physical and mental conditions that negatively affect their Quality of Life. In this article, we examined cancer and the impact that this disease can have on the Quality of Life of cancer patients. The cancers examined in this article include head and neck, prostate, breast, lung, and skin cancers. We also discussed health assessment and the importance and purpose of studying patients' Quality of Life, especially cancer patients. The various signs and symptoms of the disease that affect the Quality of Life of patients were also reviewed.